Managing the work stress of inpatient nurses during the COVID-19 pandemic: a systematic review of organizational interventions - Maria Zink; Frederike Pischke; Johannes Wendsche; Marlen Melzer (BMC, 2024)
Abstract Background During the coronavirus disease 2019 (COVID-19) pandemic, inpatient nurses faced various work stressors. Little is known about organizational interventions that can mitigate the negative consequences of pandemic-related stressors. Objective The aim was to provide a synopsis of the literature concerning the types and outcomes of organizational interventions performed during the COVID-19 pandemic that directly (re)organized the work structures of inpatient nurses to address pandemic-related work stressors or to increase nurses' ability to cope. Methods Within this preregistered systematic literature review, we searched four databases (PubMed, PsycINFO, PsycARTICLES, CINAHL) and two preprint databases (MedRxiv, PsyArXiv) for interventional studies of organizational interventions published between 01/2020 and 03/2023 (k = 990 records). We included 12 primary studies after title-abstract and full-text screening. A synthesis of results without meta-analysis was conducted. Risk of bias was assessed with the Cochrane risk-of-bias tool for randomized trials - version 2 (RoB-2) and Risk Of Bias In Non-randomized Studies - of Interventions (ROBINS-I) tool. Results All interventions were implemented in hospitals. The reasons given for implementation included pandemic-related work stressors such as a high workload, understaffing, and a lack of medical resources. To respond to the various work stressors, half of the studies took a multilevel approach combining organizational and person-oriented interventions (k = 6). Most studies (k = 8) took a secondary prevention approach, focusing on the organization of rest breaks (k = 5). With respect to outcomes, the studies examined nurse-related stress and resilience, turnover intention, job satisfaction, and other factors. Risk-of-bias analyses revealed that conclusions about the effectiveness of the interventions are limited due to confounding factors and self-selection. Conclusions The identified interventions provide a basis for future research to draw conclusions on the effectiveness of organizational interventions during pandemics. The promotion of adequate work breaks could be useful if the work stressors associated with strain and negative consequences cannot be changed directly. However, the same stressors (e.g., high workload) can hinder nurses from participating in offered interventions. This emphasizes the importance of directly addressing inpatient nurses' work stressors. Registration Prospero-ID CRD42023364807 (March 2023).